From Subordinate Partners to Dependent Employees: State Regulation of Public School Teachers in Nineteenth-Century British Columbia - Wotherspoon, Terry (Labour/Le Travailleur, 1993)
This article examines the creation and shaping of an occupation — public school teaching — in 19th century British Columbia. It represents teaching as a contractory endeavour organized around the reproduction of labour power. Drawing upon secondary accounts of teaching and state formation (supplemented with representative documents from the period of concern), the article emphasizes how struggles between different segments of the teaching force and state representatives emerged around changing moral and technical priorities. In the context of state formation and subsequent industrial development, teaching was transformed by the end of the 19th century from a relatively autonomous occupation to a highly regulated and segmented force of dependent state employees.